2019
DOI: 10.3389/fonc.2019.00587
|View full text |Cite
|
Sign up to set email alerts
|

Small Nucleolar RNAs: Insight Into Their Function in Cancer

Abstract: Small nucleolar RNAs (SnoRNAs) are a class of non-coding RNAs divided into two classes: C/D box snoRNAs and H/ACA box snoRNAs. The canonical function of C/D box and H/ACA box snoRNAs are 2'- O -ribose methylation and pseudouridylation of ribosomal RNAs (rRNAs), respectively. Emerging evidence has demonstrated that snoRNAs are involved in various physiological and pathological cellular processes. Mutations and aberrant expression of snoRNAs have been reported in cell transformation, tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
194
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(218 citation statements)
references
References 94 publications
2
194
0
3
Order By: Relevance
“…Finally, the SNORD76, a box C/D snoRNA has been shown to act as a tumor suppressor in glioblastoma [62], a similar effect observed with the depletion of jouvence in U87-MG glioblastoma cell line. In conclusion, as previously suggested [10,11], snoRNAs have the potential to become cancer biomarkers, and even may potentially become major cancer therapeutic targets in the near future. In such way, the snoRNA-jouvence is surely another good and promising candidate.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Finally, the SNORD76, a box C/D snoRNA has been shown to act as a tumor suppressor in glioblastoma [62], a similar effect observed with the depletion of jouvence in U87-MG glioblastoma cell line. In conclusion, as previously suggested [10,11], snoRNAs have the potential to become cancer biomarkers, and even may potentially become major cancer therapeutic targets in the near future. In such way, the snoRNA-jouvence is surely another good and promising candidate.…”
Section: Discussionsupporting
confidence: 59%
“…Several snoRNAs (both C/D and H/ACA boxes) have also been involved in many biological cancer processes, as tumor initiation, invasion, metastasis, and/or proliferative signalling [10,11]. For examples, some snoRNAs have been associated with the p53 pathway, a well-known tumor suppressor [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most represented group of genes in the set of highly changed ones are those encoding small nucleolar RNAs (snoRNAa), which are responsible for methylation (class C/D) or pseudouridylation (class H/ACA) of ribosomal RNA [45]. They play an important role in maturation of rRNA and regulate mRNA splicing and editing, but there is also evidence of their involvement in other processes and cellular pathways, including those related to p53 tumor suppressor or phosphoinositide 3-kinase [46].…”
Section: Gene Microarray Analysismentioning
confidence: 99%
“…Cui et al 151 found that tDR‐0009 and tDR‐7336 were notably upregulated in the SUM‐1315 cell lines stimulated by hypoxia; further, bioinformatic analysis indicated that these two upregulated tDRs might be involved in the chemoresistance to doxorubicin in TNBC via mediating the activation of phosphorylation of STAT3. As for other ncRNAs, such as snoRNA and snRNA, their tumour‐associated functions have been observed in multiple cancers, 152‐154 but no exact roles have been defined in TNBC, which need to be further explored in the future.…”
Section: Other Non‐coding Rnasmentioning
confidence: 99%